Goal setting dynamics that facilitate or impede a client-centered approach. (29th July 2019) - Kessler, Dorothy; Walker, Ian; Sauvé-Schenk, Katrine; Egan, Mary
Abstract: Background: Client-centred goal setting is central to the process of enabling occupation. Yet, there are multiple barriers to incorporating client-centred goal setting in practice. We sought to determine what might facilitate or impede the formation of client-centred goals in a context highly supportive of client-centred goal setting Methods: We used conversational analysis to examine goal-setting conversations that took place during a pilot trial of Occupational Performance Coaching for stroke survivors. Twelve goal-setting sessions were purposively selected, transcribed, and analyzed according to conventions for conversation analysis. Results: Two main types of interactions were observed: introductory actions and goal selection actions. Introductory actions set the context for goal setting and involved sharing information and seeking clarification related to goal requirements and clients' occupational performance competencies. Goal selection actions were a series of interactions whereby the goals were explored, endorsed or dropped. Conclusion: Client-centred occupational performance goals may be facilitated through placing goal-setting in the context of life changes and lifelong development of goals, and through listening to clients' stories. Therapists may improve consistency in adoption of client-suggested goals through clarifying meaning attached to goals and being attuned to power dynamics and underlying values and beliefs around risk and goal attainability.